Magnetite nanorod thermotropic liquid crystal colloids: Synthesis, optics and theory - Podoliak, Nina; Buchnev, Oleksandr; Bavykin, Dmitry V.; Kulak, Alexander N.; Kaczmarek, Malgosia; Sluckin, Timothy J. (Journal of colloid and interface science, 2012)
[Display omitted] ► Templateless preparation of magnetite nanorods by alkaline hydrothermal treatment. ► New surfactant improves magnetite nanorod–LC suspension stability. ► Strong nanorod–LC coupling leads to 20% reduction in LC Frederiks threshold. ► Theoretical model highlights routes to enhanced magneto-optical properties. ► Improved performance requires control of magnetic domains in magnetite nanorods. We have developed a facile method for preparing magnetic nanoparticles which couple strongly with a liquid crystal (LC) matrix, with the aim of preparing ferronematic liquid crystal colloids for use in magneto-optical devices. Magnetite nanoparticles were prepared by oxidising colloidal Fe(OH)2 with air in aqueous media, and were then subject to alkaline hydrothermal treatment with 10moldm−3 NaOH at 100°C, transforming them into a polydisperse set of domain magnetite nanorods with maximal length ∼500nm and typical diameter ∼20nm. The nanorods were coated with 4-n-octyloxybiphenyl-4-carboxylic acid (OBPh) and suspended in nematic liquid crystal E7. As compared to the conventional oleic acid coating, this coating stabilizes LC-magnetic nanorod suspensions. The suspension acts as a ferronematic system, using the colloidal particles as intermediaries to amplify magnetic field–LC director interactions. The effective Frederiks magnetic threshold field of the magnetite nanorod–liquid crystal composite is reduced by 20% as compared to the undoped liquid crystal. In contrast with some previous work in this field, the magneto-optical effects are reproducible on time scales of months. Prospects for magnetically switched liquid crystal devices using these materials are good, but a method is required to synthesize single magnetic domain nanorods.